Design and simulation of key mechanism for transverse sealing of fresh food packaging machine. Issue 1 (July 2021) - Zheng, Zhaoqi; Shi, Bingjian; Mei, Wenjuan; Liu, Chaoran; An, Zimin; Shi, Pu; Wang, Ruifang
Abstract: In order to improve the freshness and safety of fresh food, packaging is necessary for the processing industry of agricultural products. At present, the packaging of fresh food in China is mainly manual packaging, which has high labor intensity and low production efficiency. In response to this situation, this study focused on the transverse sealing device of the fresh food packaging machine. The device completed the transverse sealing operation through the cooperation of two main mechanisms, including an up wind box and an anthropomorphic hand folding mechanism. The anthropomorphic hand folding mechanism was composed of roller, cylinder and lower wind box. This paper makes a study of design and simulation of key mechanism for transverse sealing of fresh food packaging machine, improving the completion of the transverse sealing of the packaging machine. The experiment showed that the designed structure basically satisfied the functional requirements of the fresh food packaging machine for the sealing operation of the transverse sealing device. And the optimal parameter of the air outlet of the up wind box was 640 mm 2, the lower wind box of anthropomorphic hand folding mechanism was 19 air outlets with a diameter of 2 mm.